Assessment of Saudi Women’s Adherence and Experience with Venous Thromboembolism Prophylaxis after Cesarean Section Delivery Using Telemedicine Technology - Dalia Ahmed Elmaghraby; Zakiah Khalid Al-Bassri; Zainab Ahmed AlTuraiki; Jinan Adnan Alsaleh; Latifah Saleh Alzuwayyid; Norah Abdulmohsen Albanyan; Abdulaziz Saleh Almulhim (Applied Bionics and Biomechanics)
Background. Telemedicine technology is widely used especially after the COVID-19 pandemic. It can be used to give medical advice as well as follow up with the patients at home in the outpatient setting. Low molecular weight heparin, such as enoxaparin, decreases the risk of venous thromboembolism after cesarean delivery. Objective. assessing postcesarean women’s adherence and experience to enoxaparin thromboprophylaxis regimens in the outpatient setting via telephone calls. Methods. prospective cohort study was conducted in the Maternity and Children Hospital (MCH). Postcesarean women were interviewed at the postnatal ward in the MCH. The participants were followed up for 10 days of the delivery to assess their adherence to and experience with enoxaparin thromboprophylaxis. Suboptimal adherence was defined as the missing of one or more doses of enoxaparin. Results. 170 women participated in this study. The majority of them (78.8%) were fully adherent to enoxaparin while 21.2% missed at least one dose. The most-reported causes for suboptimal adherence were perceived lack of necessity (44.4%), forget to take the injection (30.6%), feeling of high load going to the primary care unit to take injection (27.8%), and fear of injection (11.1%). Conclusion. Telemedicine technology could be used to assess patients’ adherence. The study results showed that the majority of participants were fully adherent to postcesarean enoxaparin but more than 20% of the participants were suboptimal adherent. Proper patient education techniques could influence patients’ adherence and potentially decrease the risk of DVT in those populations.